Structure of the polymerase ε holoenzyme and atomic model of the leading strand replisome - Zuanning Yuan; Roxana Georgescu; Grant D. Schauer; Michael E. O’Donnell; Huilin Li (Nature Communications, 2020)
DNA polymerase epsilon (Pol ε) is responsible for leading strand synthesis during DNA replication. Here the authors use Cryo-EM to describe the architecture of the Pol ε holoenzyme and to provide an atomic model for the leading strand replisome.